The biological embedding of early-life socioeconomic status and family adversity in children's genome-wide DNA methylation - Bush, Nicole R (Epigenomics, 2018)
AIM: To examine variation in child DNA methylation to assess its potential as a pathway for effects of childhood social adversity on health across the life course. MATERIALS & METHODS: In a diverse, prospective community sample of 178 kindergarten children, associations between three types of social experience and DNA methylation within buccal epithelial cells later in childhood were examined. RESULTS: Family income, parental education and family psychosocial adversity each associated with increased or decreased DNA methylation (488, 354 and 102 sites, respectively) within a unique set of genomic CpG sites. Gene ontology analyses pointed to genes serving immune and developmental regulation functions. CONCLUSION: Findings provided support for DNA methylation as a biomarker linking early-life social experiences with later life health in humans.